Chiral CuxOS@ZIF‐8 Nanostructures for Ultrasensitive Quantification of Hydrogen Sulfide In Vivo. Issue 19 (6th April 2020) - Yuan, Aimeng; Hao, Changlong; Wu, Xiaoling; Sun, Maozhong; Qu, Aihua; Xu, Liguang; Kuang, Hua; Xu, Chuanlai
Abstract: In this study, a Cu x OS@ZIF‐8 nanostructure is fabricated to quantify the levels of hydrogen sulfide (H2 S) in living cells and in vivo. Zeolitic lmidazolate framework‐8 (ZIF‐8) is chosen as an encapsulation shell to improve the selectivity of this probe. Using this unique nanostructure, ultrasensitive quantification and bioimaging of H2 S in living cells are successfully achieved. The lower limit of detection is 0.8 and 5.3 nmol per 10 6 cells for circular dichroism and fluorescence modes, respectively. It is found that the chiral Cu x OS NPs transformed into achiral Cu x S NPs contribute to the ultrasensitive detection. Notably, this probe can also be carried out to detect and track H2 S levels in tumor‐bearing animals. The discoveries put forward for the creation of a detection platform for quantitative tracking and analysis in clinic. Abstract : A Cu x OS@ZIF‐8 nanoprobe is fabricated for the sensitive and selective detection of H2 S in vitro and in vivo through circular dichroism and fluorescent dual signals. It is discovered that the chiral Cu x OS is transformed into achiral Cu x S to contribute to the ultrasensitive detection. The developed probes demonstrate a biomolecule toolbox for quantitative analysis in life science.